Electronic monitoring of adherence to inhaled medication in asthma - Howard, Sam; Lang, Alexandra; Patel, Mitesh Dilipkumar Kantilal; Sharples, Sarah; Shaw, Dominick E. (Bentham Science, 2014)
The main treatment of asthma is inhaled corticosteroids. However adherence to these medications in asthma is often poor, with low adherence associated with excessive health care costs and an increased risk of emergency room visits and mortality. Although various methods are used to indirectly assess adherence, all have significant limitations whether used in clinical or research practice. The recent development of electronic monitoring devices (EMDs) for use with inhalers presents an exciting opportunity to easily and accurately measure inhaler adherence. This article summarises the current devices available; for each device features and limitations are considered, followed by a review of both the current clinical literature and data on reliability and accuracy. An overall summary is also provided to aid comparison of capabilities between devices and future issues pertaining to the use of EMDs are discussed, including barriers to adoption, stakeholder involvement, novel methods of communicating adherence data, recording of data and cloud storage. Finally key areas that still require investigation are highlighted.